Accelerated Microbial Degradation of Nematicides in Vineyard and Orchard Soils - Hugo, H.J.; Mouton, C.; Malan, A.P. (South African Journal of Enology and Viticulture, 2016)
Accelerated microbial degradation (AMD) of organophosphate and carbamate nematicides is a phenomenon whereby biodegradation in the soil is increased, leading to a dramatically shortened persistence of nematicides. More intensified agriculture practices in South Africa in response to the future demand for food may lead to increased pest and disease pressure, which in turn will lead to more frequent pesticide application. The same principle applies to plant-parasitic nematode control practices, and the overuse and misuse will have a pronounced effect on the enhancement of AMD. With limited management options available, the responsible use of nematicides becomes more pertinent. Producers should be aware of the problems associated with multiple soil applications of organophosphates and carbamates against plant-parasitic nematodes. This article reviews factors contributing to the AMD of carbamate and organophosphate nematicides in soil and makes practical recommendations to avoid the occurrence of AMD in vineyard and orchards.